Diepoxybutane-induced apoptosis is mediated through the ERK1/2 pathway. (October 2018) - Eluka-Okoludoh, E; Ewunkem, AJ; Thorpe, S; Blanchard, A; Muganda, P
Diepoxybutane (DEB) is the most potent active metabolite of butadiene, a regulated air pollutant. We previously reported the occurrence of DEB-induced, p53-dependent, mitochondrial-mediated apoptosis in human lymphoblasts. The present study investigated the role of the extracellular signal–regulated protein kinases 1 and 2 (ERK1/2) pathway in DEB-induced apoptotic signaling in exposed human lymphoblasts. Activated ERK1/2 and mitogen-activated protein (MAP) kinase/ERK1/2 kinase (MEK) levels were significantly upregulated in DEB-exposed human lymphoblasts. The MEK inhibitor PD98059 and ERK1/2 siRNA significantly inhibited apoptosis, ERK1/2 activation, as well as p53 and phospho-p53 (serine-15) levels in human lymphoblasts undergoing DEB-induced apoptosis. Collectively, these results demonstrate that DEB induces apoptotic signaling through the MEK-ERK1/2-p53 pathway in human lymphoblasts. This is the first report implicating the activation of the ERK1/2 pathway and its subsequent role in mediating DEB-induced apoptotic signaling in human lymphoblasts. These findings contribute towards the understanding of DEB toxicity, as well as the signaling pathways mediating DEB-induced apoptosis in human lymphoblasts.